Attentional Resource Allocation in Visuotactile Processing Depends on the Task, But Optimal Visuotactile Integration Does Not Depend on Attentional Resources - Wahn, Basil; König, Peter (Frontiers in Integrative Neuroscience, 2016)
Humans constantly process and integrate sensory input from multiple sensory modalities. However, the amount of input that can be processed is constrained by limited attentional resources. A matter of ongoing debate is whether attentional resources are shared across sensory modalities, and whether multisensory integration is dependent on attentional resources. Previous research suggested that the distribution of attentional resources across sensory modalities depends on the the type of tasks. Here, we tested a novel task combination in a dual task paradigm: Participants performed a self-terminated visual search task and a localization task in either separate sensory modalities (i.e., haptics and vision) or both within the visual modality. Tasks considerably interfered. However, participants performed the visual search task faster when the localization task was performed in the tactile modality in comparison to performing both tasks within the visual modality. This finding indicates that tasks performed in separate sensory modalities rely in part on distinct attentional resources. Nevertheless, participants integrated visuotactile information optimally in the localization task even when attentional resources were diverted to the visual search task. Overall, our findings suggest that visual search and tactile localization partly rely on distinct attentional resources, and that optimal visuotactile integration is not dependent on attentional resources.